What factors influence tourists’ decision to visit ecotourism destinations in Bangladesh? - Rahman, Mohammad Moshiur; Haque, A. K. M. Ahasanul; Suib, Fatin Husna (University of Oradea, Romania, 2023)
Ecotourism has been recommended for multiple outcomes that foster environmental protection in developing nations. Tourism studies have revealed that ecotourism has several setbacks in Bangladesh, resulting in environmental difficulties, security issues and tourists’ unwillingness to visit destinations. Therefore, this paper examines the factors of destination image, perceived risk, and travel motivation to foresee tourists’ selection of ecotourism destinations in Bangladesh. The framework of this study is built upon the “Stimulus-Response Model of Buyer Behaviour” to address the knowledge gap. A total of 364 usable responses were collected from the tourists. The data were examined using SPSS for primary analysis and SEM-AMOS for hypothesis testing. The findings suggest that a proper image and motivation would encourage tourists to visit ecotourism destinations.